Cultivating Students’ Creativity and Reading Encouragement by Integrating Ecopedagogy Extensive Reading and Digital Project - Mardiana, Wiwik; Feriyanto, Feriyanto; Maulia, M. Lorna (International Journal of Education, Information Technology, and Others, 2023)
The beneficial impacts of both extensive reading and digital project have been proved by some scholars to improve the students’ competencies. Besides, the environmental crisis in today’s era also needs to be executed. This research explains how ecopedagogy extensive reading and digital storytelling project stimulates students’ creativity and enhances reading encouragement as well as environmental awareness during the learning process. Thirty-six senior high school students were involved in this study. The data were obtained from students’ writing artifacts, classroom observations, and interviews. Employing qualitative case study, the results reveal that ecopedagogy extensive reading help senior high school students discover, express, and compose idea as well as cultivate their creativity in writing narratives. Specifically, the ecopedagogy approach used help students be aware of environmental problem and express the solution in their writing. This study recommends that using both extensive reading activities and digital writing projects is influential in enhancing students reading motivation, writing ability, and creativity.